Fascist spectacle : the aesthetics of power in Mussolini's Italy - Falasca-Zamponi, Simonetta, 1957- (University of California Press, 1997)
At the end of October 1922, in a whirlwind of events and unexpected circumstances, Benito Mussolini became prime minister of Italy. For the next twenty years, he dominated Italy as a cult hero and the duce of fascism and, later, founder of the empire. This richly textured cultural history traces the narrative path that accompanied the making of the fascist regime and the construction of Mussolini's power. Simonetta Falasca-Zamponi reads fascist myths, rituals, images, and speeches as texts that tell the story of fascism. Linking Mussolini's elaboration of a new style of rule to the shaping of the regime's identity, she finds that in searching for symbolic means and forms to represent its political novelty, fascism actually created its own power, its own happening, its history.
Keywords: Fascism -- Italy.; Italy -- Politics and government -- 1922-1945.; Fascism and culture -- Italy.; Aesthetics, Italian -- 20th century.; Fascisme -- Italie.; Italie -- Politique et gouvernement -- 1922-1945.; Fascisme et culture -- Italie.; POLITICAL SCIENCE -- Political Ideologies -- Fascism & Totalitarianism.; HISTORY / Europe / General; Aesthetics, Italian; Fascism; Fascism and culture; Politics and government; Italy; Fascisme.; Machtsvertoon.; Theatraliteit.; Italië; Fascisme -- Italie -- 1900-1945.; Esthétique italienne -- 1900-1945.; 1900-1999